Effect of Monosodium Glutamate and L-Carnitine on Density and Structure of Granular Cells of Cerebellum in Rat - Mojdeh Fatahzadeh; Mohammad Amin Edalatmanesh (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2018)
Abstract Background: Monosodium glutamate (MSG) is a widely-used flavor enhancer and stabilizer in ready-made or packaged foods. The excessive use of MSG has been shown to increase oxidative stress in different regions of the brain. In this study, the neuroprotective effect of L-carnitine was investigated against MSG intoxication in granular cell of cerebellum in rats. Materials and Methods: 48 adult male Wistar rats were randomly divided into 6 groups: the control, sham (normal saline treated), MSG (3%), L-Carnitine200, MSG+L-Carnitine100 and MSG+L-Carnitine200. After 30 days of treatment, through transcardialy perfusion, the rats were sacrificed and histopathological analyses were conducted on cerebellum. Results: The results indicated that the density of granular cells in cerebellar folium IV, V and VI of rats in the MSG group had significantly decreased in comparison to that of the control and sham groups. Furthermore, the MSG+L-Carnitine200 group showed the higher density of granular cells compared with the MSG group in the three folia. Conclusion: Treatment with L-Carnitine could protect the granular cells in cerebellum against MSG intoxication in rats.